2017
DOI: 10.1007/s13730-017-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi syndrome and neonatal diabetes: phenotypic heterogeneity in patients with GLUT2 defects

Abstract: Fanconi-Bickel syndrome, caused by mutations in SLC2A2 encoding the glucose transporter 2 (GLUT2), is characterized by generalized proximal renal tubular dysfunction manifesting in late infancy. We describe phenotypic heterogeneity of Fanconi-Bickel syndrome in three siblings, including early and atypical presentation with transient neonatal diabetes mellitus in one. The second-born of a non-consanguineous couple, evaluated for polyuria and growth retardation, had rickets, hepatomegaly and proximal tubular dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
4
14
0
1
Order By: Relevance
“…GluT2, the major mediator of glucose uptake by hepatocytes and pancreatic β-cells is decreased in patients with dM (25)(26)(27). The present study demonstrated that PdM mice had decreased levels of GluT2 mrna, which led to the impaired uptake of glucose and secretion of insulin.…”
Section: Discussionsupporting
confidence: 46%
“…GluT2, the major mediator of glucose uptake by hepatocytes and pancreatic β-cells is decreased in patients with dM (25)(26)(27). The present study demonstrated that PdM mice had decreased levels of GluT2 mrna, which led to the impaired uptake of glucose and secretion of insulin.…”
Section: Discussionsupporting
confidence: 46%
“…Since the initial report of transient neonatal diabetes by Sansbury et al [ 74 , 106 ], two more cases have been described with homozygous SLC2A2 gene mutations. Yoo et al (2002) reported a newborn with transient neonatal diabetes and galactosemia with a novel SLC2A2 homozygous gene mutation [ 83 ], and Khandelwal et al (2018) reported phenotypic heterogeneity in siblings with one of the siblings having transient neonatal diabetes [ 55 ]. The findings of transient neonatal diabetes in some cases of FBS suggest an important role of GLUT2 in human β-cell physiology.…”
Section: Slc2a2 (Glut2) Mutations and Patterns mentioning
confidence: 99%
“…Clinical characteristics of FBS may include hepatomegaly related to hepatic and renal glycogen accumulation, renal proximal tubular dysfunction characterized by glucosuria and phosphate wasting often leading to hypophosphatemic rickets, delay of puberty and short stature, hypergalactosemia (which may be identified by newborn screening), and mild fasting hypoglycemia but postprandial hyperglycemia and diabetes or impaired glucose tolerance at many ages of onset, including during infancy [93, 94]. The heterogeneity of this syndrome was further elucidated in a recent report of three siblings, one of whom had transient infancy-onset diabetes (onset around 2 weeks old, remission at 3 months old), as well as hepatomegaly, phosphaturia, hypercalciuria, aminoaciduria, and proximal renal tubular acidosis [95]. Diabetes was not present in the other two siblings, although one did experience fasting hypoglycemia, and unfortunately, they both died (age 4 months and age 6 years).…”
Section: Rarer Causes Of Congenital Diabetesmentioning
confidence: 99%